Chemically Composite Ceramic Wear Sealant Materials
Patent Information
- Application Number
- JP2023557163
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-17
- Filing Date
- 2022-03-16
- Publication Date
- 2025-02-18
AI Technical Summary
Conventional ceramic abradable coatings in turbomachinery suffer from reduced erosion resistance and hardness, leading to blade abrasion and damage, particularly in high-temperature environments, due to their porous nature and reliance on filler phases.
The use of high entropy oxide (HEO) ceramic-based abradable sealant materials with a chemically inert film and high configurational entropy, which enhances cutting performance and thermal stability, eliminating the need for polymeric fillers and improving resistance to chemical attack and abrasion.
The HEO coatings exhibit superior wear performance, thermal stability, and resistance to CMAS attack, reducing blade abrasion and enhancing the operational lifespan of turbine blades by forming a high-porosity film that minimizes contact with rotating components.
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of and priority to U.S. Provisional Application No. 63 / 162,228, filed March 17, 2021, the disclosure of which is expressly incorporated by reference in its entirety herein.
[0002] 2. Background of the Invention 1. Field of disclosure The present disclosure relates to thermally sprayed feedstock materials and abradable sealant coatings having high entropy oxides (HEOs) for increasing engine efficiency in the high temperature regions of turbine engines. [Background technology]
[0003] 2. Background Information In turbomachinery, abradable seals are used to reduce the clearance between rotating members (e.g., blades and labyrinth seal knife edges) and the engine casing. Reducing the clearance between the rotating members and the engine casing improves the efficiency of the turbine engine, lowering fuel consumption and reducing the safety margin of the clearance by eliminating the possibility of fatal contact between the blades and the engine casing. An abradable seal is manufactured by applying an abradable coating to a stationary part (the engine casing) that rubs off when it comes into contact with the tips of the rotating members (e.g., blades or knife edges) during operation. This process virtually eliminates the gap between the blade tips and the internal engine housing.
[0004] Conventional thermal spray powders produce abradable coatings for clearance control applications where rotating components may contact the coating due to design intent or surge during operation. The coatings are designed to minimize wear on the rotating components while maximizing gas path efficiency by providing clearance control in the sealed area. Depending on the operating conditions required for the engine sections of various engines, conventional abradable seals may be oxide ceramics or aluminum, copper, cobalt, and / or nickel-based metal alloys. In hot engine sections, conventional abradable seal materials often include zirconia-based ceramics stabilized with rare earth oxides, such as yttria, ytterbia, and / or dysprosia. These coating concepts combine the desirable properties of high temperature ceramics with polymeric materials to create porosity in the coating (e.g., Metco 2395 8YSZ + 4.5 wt% polyester + 0.7 wt% hBN or M2460NS 8YSZ + 4.0 wt% polyester). These coatings are suitable for abrasive attack on either bare untipped nickel alloy blades or tipped nickel alloy turbine blades. Summary of the Invention [Problem to be solved by the invention]
[0005] To reduce blade wear, the mechanical properties of the ceramic abradable coating need to be modified so that the ceramic can be easily cut by the blade without causing significant blade wear. Conventional ceramic abradable coatings use high porosity or filler phases that reduce the overall erosion resistance and hardness of the coating, allowing the abradable coating to be cut. [Means for solving the problem]
[0006] overview The present disclosure provides a thermal spray material feedstock that forms a coating with extremely low erosion resistance (excellent wear performance), high thermal stability, and chemical inertness. The use of high entropy oxides in ceramic-based abradable sealant materials improves the cutting performance of ceramic-based abradable coatings and eliminates abrasion damage to (1) nickel alloy turbine blades (e.g., turbine sections of aircraft engines or land-based gas steam turbine engines) and (2) nickel alloy turbine blades with tips (e.g., turbine sections of aircraft engines or land-based gas steam turbine engines). The use of ceramic abradable coatings made from high entropy oxides also improves thermal stability and sintering resistance, resulting in higher service temperatures. Resistance to chemical attack by calcia-magnesia-alumino-silicate (CMAS) is also a desirable property exhibited by HEO. Another advantage of HEO-based ceramic abradable sealant materials is that their brittle nature does not require the use of polyester as a temporary phase to create high porosity levels in the coating structure and achieve superior wear performance.
[0007] "Excellent wear performance" is defined as low blade abrasion damage obtained.
[0008] "Blade abrasion damage" is defined in one of two ways: (1) two-body abrasive abrasion of the blade material due to the ceramic material components in the abradable coatings based on the designated 8 wt. % yttria-stabilized zirconia (YSZ) polyesters (Metco 2395 and Metco 2460NS), 48 wt. % yttria-stabilized zirconia (YSZ) polyester (Metco 2461A), dysprosia-stabilized zirconia (DySZ) polyester (Durabrade 2192), ytterbia zirconia polyester (Durabrade 2198), and magnesia aluminate spinel (Metco 2245); and (2) severe abrasion damage resulting from excessive heating of the blade material caused by severe frictional abrasion conditions in the turbine and / or the abradable coating is thermally sprayed at excessively high bulk hardness conditions.
[0009] Examples of severe abrasion damage include heat-softened blade material, severe bulk plastic deformation, and cracking. Another example of severe abrasion damage includes oxidation of blade material resulting from friction-induced heating. A further example of severe abrasion damage includes burning of blade material (mainly limited to titanium alloys). Yet a further example of severe abrasion damage includes cracking of blade material due to extreme blade cutting forces resulting from inefficient cutting against an abrasive shroud with a higher than certain hardness.
[0010] Exemplary embodiments of the present disclosure relate to thermal spray material feedstocks that include chemical compounds or "high entropy" oxides (HEOs) as abradable sealing coatings. HEOs allow precise control of chemical, mechanical, and thermal properties for use in specific environments. In embodiments, the HEOs of the present disclosure do not include any major constituent oxides, such as zirconia in stabilized zirconia coatings. In embodiments, the abradable sealing coatings contain at least five major oxide constituents at high concentrations of >5 mol%.
[0011] In an exemplary embodiment, the abradable sealing coating comprises a sublattice having a mixture of five or more cations and at least one sublattice containing oxygen. The random arrangement of the five or more cations results in a high configurational entropy (S config ) materials. The inclusion of five or more elements also provides the ability to modify the phase composition to enhance wear and chemical resistance in certain environments. The inclusion of five or more elements also provides high configurational entropy of the individual phases, resulting in increased thermal stability. Thermal properties, such as thermal conductivity, can also be modified by the inclusion of specific constituents, resulting in superior performance.
[0012] HEOs have large lattice strains and other defect concentrations that result in low thermal conductivity. Because of their characteristically low thermal conductivity, HEOs have been investigated as thermal barrier coatings for turbine engines, but the use of HEOs as abradable seal coatings has not been previously studied.
[0013] The present disclosure provides a new class of ceramic abradable seal compositions that exhibit improved abrasion and wear behavior (wear performance). Depending on the type of HEO used, improved thermal properties, excellent sintering resistance, excellent phase stability, good thermal cycling performance, and high resistance to chemical attack (e.g., by CMAS) can be obtained in the abradable seal coatings of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Detailed Description In some embodiments, the oxide ceramic is used as a sealant material or an abradable seal material. In an exemplary embodiment, the oxide ceramic has a complex atomic composition of the general formula M x O y where M is selected from the group of at least five different oxide-forming metal cations in an amount greater than 5 mol %. x O y is a standard metallurgical abbreviation. For example, carbides (Cr,Mo,W,Fe) 23 C6 is generally M 23 C6, and (TiNbTaZrHf)C is called MC. Similarly, M x O y are oxides (Zr, Ce, Y, Yb, Gd, Dy) x O y where "M" is selected from the group of at least five oxide-forming metals.
[0015] In one embodiment, the configurational entropy S of the oxide ceramic config is greater than 1.5 R per mole, where R is the gas constant 8.314 J K -1 mol -1 This S config is the commonly accepted definition of a high entropy material. In embodiments, the metal cations "M" and oxygen anions "O" can be allocated to one or more crystal sublattices.
[0016] In embodiments of the present disclosure, the metal "M" is a non-toxic, non-radioactive oxide-forming metal, e.g. Alkaline earth metals including Be, Mg, Ca, Sr, and Ba; Transition metals, including Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Re, Fe, Ru, Co, Ni, Cu, and Zn; It can include lanthanides, including La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, and Lu.
[0017] For example, "M" is selected from the group of at least five different oxide-forming metal cations including at least one alkaline earth metal, at least one transition metal, and at least one lanthanide. In another example, "M" is selected from the group of at least five different oxide-forming metal cations among the alkaline earth metals, transition metals, and lanthanides.
[0018] In embodiments, the following metals can be used in the HEO abradable seal coating: (1) alkaline earth metals, such as Mg and Ca, (2) transition metals, such as Y, Ti, Zr, Hf, V, Cr, Mo, and W, and (3) lanthanides, such as La, Ce, Pm, Sm, Eu, Gd, Tb, Dy, Er, and Yb.
[0019] In embodiments, the metal cations "M" and oxygen anions "O" can be allocated to one or more crystal sublattices. Thus, the oxides of the present disclosure can be allocated to the previously unknown crystal lattices (Zr,Y,Yb,Gd,Dy) x O y or it can compartmentalize itself into two or more commonly known crystal lattices, e.g. (Y,Yb,Gd,Dy)2O3 and (Zr,Ce)O2. In the latter case, this means two atoms from the group (Y,Yb,Gd,Dy) for every three oxygen atoms, and one atom from the groups Zr and Ce for every two oxygen atoms in the overall composition. These oxide lattices are expected to be intimately intermixed, such that scanning electron microscopy cannot detect separate phases in the HEO structure.
[0020] Two fundamental differences between the embodiments of the present disclosure and the Nicoll et al., Dieter et al., and Xie et al. references (listed below): 1. High entropy (S config is greater than 1.5R) (which can be calculated for any composition using standard thermodynamic formulas, e.g., as described in Ref. 1), and 2. Contains a greater number of "M" species.
[0021] The fundamental difference between the embodiments of the present disclosure and the He et al. references (listed below) is that 1. Use of high entropy oxides as abradable sealing materials.
[0022] While high entropy oxides have been used as thermal barrier coatings, the use of high entropy oxides as abradable seals is not known. For example, see Harrington's reference (listed below as Ref. 16), which states that "(As a starting point and baseline, the four main cations (Hf 0.25 Zr 0.25 Ce 0.25 Y 0.25 )O 2-δ "In addition to the fluorite oxides, 11 fluorite oxides with five major cations were prepared by high-energy ball milling, spark plasma sintering, and annealing in air."
[0023] In some embodiments of the present disclosure, the high entropy oxide abradable coating is further resistant to calcia-magnesia-alumina-silica (CMAS). CMAS resistance is not an inherent feature of high entropy oxides, but is an independent property useful for abradable coatings. CMAS resistance is typically measured by placing a CMAS material on top of the oxide coating to be tested, exposing the fabricated test coupons to elevated temperatures, and measuring the penetration of CMAS into the oxide coating.
[0024] In an exemplary embodiment, the oxide is subjected to a test temperature of 1250° C. for 8 hours with a CMAS composition having a melting temperature of 1110-1125° C. at 8 hours. Unless otherwise stated, all CMAS penetration data presented in this disclosure was tested under these conditions.
[0025] It was found that HEO coatings exhibited higher resistance to molten silicate attack than 7YSZ. The addition of alkaline earth oxides ("AE") can further enhance the resistance of high entropy oxides. The addition of AE has two effects: 1) increasing the melting temperature of the phase that forms at the interface between the thermal barrier coating ("TBC") and the molten silicate, and 2) providing elements (e.g., Ca, Mg, and RE) necessary for the formation of the protective layer in the coating as well as in the molten silicate. This kinetics has been shown to modify the kinetics of the phase formation of the protective layer, resulting in the formation of a preferred dense protective layer rather than an acicular morphology.
[0026] Indeed, when molten silicate reacts with a coating containing transition metal oxides (e.g., ZrO2) and Y and / or other rare earth dopants, the rare earth dopants that form the most stable high temperature phase (e.g., apatite) are preferentially leached out of the coating.
[0027] High Y zirconia coatings, such as 48YSZ, can efficiently form a moderate protective apatite in the CMAS barrier. The desired protective layer is an apatite-type layer with AE2+yRE8+x(SiO4)6O2+3x / 2+y. Including both rare earths and alkaline earths in varying amounts in the coating can manipulate the apatite phase growth kinetics by changing the concentration gradient, since the layer contains both the RE and AE elements of CMAS. When the AE and RE concentrations in the coating are both high, Si diffuses from the molten CMAS into the coating to form apatite. When AE is not included in the coating, the RE elements diffuse from the coating to form apatite with the silicates contained in the CMAS. The apatite that forms from Si diffusion into the coating is more protective.
[0028] This effect is particularly important in high entropy or complex concentrated oxides, since it is much more evident when alkaline earth metals are present in solution with transition metal oxides (in this case ZrO2, HfO2, TiO2, Y2O3, Nb2O5, V2O5, Ta2O5, Cr2O3, MoO3, WO3) and rare earth oxides of the lanthanide series (La2O3, CeO2, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Yb2O3, and Lu2O3) and any mixtures thereof, than in separate phases. The basic principle is to prevent the diffusion of AE and RE elements from the film into the CMAS and to allow Si to diffuse into the film to form the apatite phase. A highly disordered single-phase solid solution containing the RE and AE elements further retards their diffusion out of the material.
[0029] An embodiment of the present disclosure includes a mixture of oxides containing transition metals, rare earth oxides of the lanthanide series, and alkaline earth metals. In an embodiment, the alkaline earth oxides change the formation kinetics of the apatite layer that forms at the interface between the protective coating and the molten silicate. The kinetics results in a completely dense continuous layer between the molten silicate and the solid coating. In conventional coatings, such as 7YSZ, the apatite layer is not protective and leaching of the coating material is rapid and uninhibited.
[0030] In an embodiment of the present disclosure, the protective layer that forms at the boundary is a complex oxide containing alkaline earth elements (i.e. Be, Mg, Ca, Sr, and Ba), yttrium or rare earth elements (i.e. Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu), and Si. When the source of AE and / or Si is only in the molten silicate or in the CMAS, the morphology of the layer is needle-like and minimally protective. When the AE necessary for the formation of a protective boundary phase is found in the coating, the morphology of the coating is dense and continuous at the boundary. This provides a protective effect and prevents further leaching of RE and AE elements from the coating.
[0031] An exemplary embodiment of the present disclosure includes a coating containing at least four group A compounds and one group B compound. The group A compounds include ZrO2, HfO2, TiO2, Y2O3, Nb2O5, V2O5, Ta2O5, Cr2O3, MoO3, WO3, La2O3, CeO2, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Yb2O3, and Lu2O3. The group B compounds include MgO, CaO, CaCO3, SrO, SrCO3, BaO, and BaCO3. In an embodiment, a coating composition is provided in which the protective layer is not of the apatite type, but is still controlled by including AE and RE elements in the composite solution of the coating.
[0032] In some embodiments, it is desirable to reduce the content of costly oxides, typically formed from rare earth metals, in order to minimize raw material costs. In an embodiment, the rare earth metals include yttrium, gadolinium, neodymium, dysprosium, hafnium, niobium, and tantalum. In one embodiment, it is desirable to minimize the content of costly oxides, including at least one of Hf-oxide, Ta-oxide, Dy-oxide, Nb-oxide, Nd-oxide, Gd-oxide, and Y-oxide, to less than 55 wt%. In an embodiment, the costly oxides include any stoichiometry between metal species and oxides. In a preferred embodiment, the costly oxide content of the HEO is less than 50 wt%. In a more preferred embodiment, the costly oxide content of the HEO is less than 45 wt%. By way of comparison, gadolinium zirconate, a known CMAS-resistant oxide mentioned in this disclosure, has 59-60 wt% gadolinium, thus equating to a costly oxide content of 59-60 wt%.
[0033] In some embodiments, the chemical structure of HEO is 5-14% by weight of alkaline earth metal oxides, such as CaCo3, CaO, or MgO; 35-70% by weight of a rare earth metal oxide, such as Yb2O3, Gd2O, or Sm2O3; 13-57 wt.% ZrO2, and Contains 6-20% by weight of Y2O3.
[0034] In some embodiments, Al2O3 can be added up to 3 wt.%. In other embodiments, La2O3 or other sources of La are specifically limited to less than 2 wt.%. In some embodiments, all sources of La are limited to less than 0.5 wt.%.
[0035] In an embodiment, the chemical structure of HEO (representing the chemical structure of HEO-2) is 11-17% by weight of alkaline earth metal oxides, e.g. CaCO3, 55-83% by weight of a rare earth metal oxide, such as Yb2O3, Gd2O3, or Y2O3; 22-33 wt% Yb2O3, 20-31% by weight of Gd2O3, 12-19 wt.% Y2O3, and Contains 13-21% by weight of ZrO2.
[0036] In an embodiment, the amount of alkaline earth metal oxide is 12.5-15.5 wt%. In an embodiment, the amount of rare earth metal oxide is 61-76 wt%. In another embodiment, the amount of rare earth metal oxide is 22-33 wt%. In an embodiment, the amount of Y2O3 is 14-18 wt%. In an embodiment, the amount of ZrO2 is 15-19 wt%.
[0037] In an embodiment, the chemical structure of HEO (representing the chemical structure of HEO-8) is 5-9% by weight of an alkaline earth metal oxide, e.g. MgO; 41-63 wt. % rare earth metal oxides, e.g., 1-2 wt. % La2O3 and 24-38 wt. % Gd2O3; Preferably, the content of expensive oxides Y2O3 and Gd2O3 is less than 55% by weight; 15 to 24% by weight of Y2O3, and The balance is ZrO2.
[0038] In an embodiment, the amount of alkaline earth metal oxide is 6-8 wt%. In an embodiment, the amount of rare earth metal oxide is 46-58 wt%. In an embodiment, the amount of rare earth metal oxide is 22-33 wt%. In an embodiment, the amount of Y2O3 is 14-18 wt%. In an embodiment, the amount of ZrO2 is 15-19 wt%. In an embodiment, the amount of Y2O3 is 17-22 wt%.
[0039] In an embodiment, the chemical structure of HEO (representing the chemical structure of HEO-9) is 4-7 wt. % alkaline earth metal oxides, for example 2-4 wt. % CaO and 1-3 wt. % MgO; 28-43% by weight of rare earth metal oxides, such as 8-13% by weight of Yb2O3, 7-12% by weight of Gd2O3, 7-12% by weight of Sm2O3, 4 to 8% by weight of Y2O3, and The balance is ZrO2.
[0040] Preferably, the content of the costly oxides Y2O3, Yb2O3, and Gd2O3 is less than 40% by weight.
[0041] In an embodiment, the amount of rare earth metal oxide is 32-40 wt.%. In an embodiment, the amount of Y2O3 is 5-7 wt.%.
[0042] In an embodiment, the chemical structure of the HEO (representing the chemical structure of HEO-10) is 8 to 14% by weight of alkaline earth metal oxides, for example 5 to 8% by weight of CaO and 3 to 6% by weight of MgO; 60-91 wt. % rare earth metal oxides, e.g., 18-27 wt. % Yb2O3, 16-25 wt. % Gd2O3, and 15-24 wt. % Sm2O3; 4 to 16% by weight of Y2O3, and The balance is ZrO2.
[0043] In one embodiment, the amount of Y2O3 is 10-16 wt.%. In another embodiment, the amount of Y2O3 is 4-8 wt.%.
[0044] In some embodiments, the HEO has high CMAS resistance as demonstrated by a low penetration depth when subjected to the CMAS test conditions described above. In some embodiments, the CMAS penetration depth is less than 100 μm. In other embodiments, the CMAS penetration depth is less than 85 μm. In yet other embodiments, the CMAS penetration depth is less than 70 μm.
[0045] As previously mentioned, CMAS resistance is not an inherent property of HEO materials, and it has been experimentally found by the inventors that some experimental HEOs have high CMAS penetration depths. For example, a conventional TBC coating of 7YSZ was found to have a CMAS penetration depth of >400 μm. As another example, a TBC coating of GZO, another widely used TBC known in part for its improved CMAS resistance over 7YSZ, was found to have a CMAS penetration of about 150 μm.
[0046] In an embodiment, the oxides of the present disclosure have high CMAS resistance as demonstrated by the formation of apatite phase. The inventors have found that elevated amounts of alkaline earth metals enhance CMAS resistance. However, it has also been found that excessively high alkaline earth metal content can shift the reaction products to phases other than apatite. For example, some experimental compositions with high Mg content that form olivine have been produced. Therefore, it is required to balance the alkaline earth metal content so as not to overdo the oxide and shift the reaction products to phases other than apatite.
[0047] In some embodiments, the oxide of the present disclosure comprises one component of an abradable coating. In other embodiments, the abradable coating comprises one or more of the following: (1) a pore former, such as polyester, polymer, polyimide, and / or PMMA, (2) a solid lubricant, such as graphite, hBN, or calcium fluoride, and (3) another filler phase, such as talc or clay, or a metal alloy.
[0048] Moreover, since at least the invention is disclosed herein to enable it to be made and used, e.g., by way of simplicity or efficiency, by disclosure of specific exemplary embodiments, the invention can be practiced without any additional elements or additional structure not specifically disclosed herein.
[0049] It should be noted that the above examples are provided for illustration only and are not to be construed as limiting the present invention in any way. Although the present invention has been described with reference to exemplary embodiments, it is understood that the words used herein are words of description and explanation, rather than words of limitation. Changes may be made within the scope of the appended claims, as currently described and as amended, without departing from the scope and spirit of the present invention in its aspects. Although the present invention has been described herein with reference to specific means, materials and embodiments, the present invention is not intended to be limited to the particulars disclosed herein, but rather the present invention extends to all functionally equivalent structures, methods and uses, for example, within the scope of the appended claims. Prior art references All references below are incorporated herein by reference. US Patent: 1. U.S. Patent 4421799 E.R. Novinski 2. US Patent 4578114 S. Rangaswamy 3. US Patent 5059095 BA Kushner 4. US Patent 5997248 F. Ghasripoor 5. US Patent 6812176 D. Zhu 6. US Patent 6887528 Y. Lau 7. US Patent 7001859 D. Zhu 8. US Patent 7186466 D. Zhu 9. U.S. Patent 8187717 L. Xie 10. US Patent 9581041 RJ Sinatra 11. U.S. Patent 9975812 J.C. Doesburg US Patent Documents: 12. 2005 / 0196271A1 September 8, 2005 WILSON 13. 2009 / 0060747A1 March 5, 2009 STROCK 14. 2011 / 0164963A1 July 7, 2011 TAYLOR 15. 2018 / 0022928A1 January 25, 2018 BLUSH 16. 2018 / 0022929A1 January 25, 2018 BLUSH 17. 2018 / 0298776A1 October 18, 2018 STROCK 18. 2018 / 0128952A1 May 10, 2018 YEH 19. 2020 / 0003125A1 January 2, 2020 AMINI 20. 2020 / 0141260A1 May 7, 2020 SEYMOUR Australian Patent Publications: 21. 2014 / 221259A1 October 2, 2014 LEACH Canadian Patent: 22. Canadian Patent 2431310 D. Mitchell 23. Canadian Patent 2488949 W. Scott 24. Canadian Patent 2549600 N. Andrew 25. Canadian Patent 2585992 S. Dieter 26. Canadian Patent 2686332 M. Cybulsky 27. Canadian Patent 2880147 M. Podgorski 28. Canadian Patent 2914289 R. Larry 29. Canadian Patent 3051995 A. Bolcavage European Patent: 30. European Patent 0455996 K. Burton 31. European Patent 1371815 F. Braillard 32. European Patent 1548144 W. Scott 33. European Patent 1500790 F. Gross 34. European Patent 2683844 K. Lee 35. European Patent No. 3141704 Y. Kojima 36. European Patent No. 3369487 T. Kurimura 37. European Patent 3597860 K. Seymour 38. European Patent No. 3597871 R.W. Jackson 39. European Patent 3623355 WR Schmidt Spanish patent: 40. Spanish Patent 2355152 W. Scott International patent publications: 41. 2003 / 059529A1 July 24, 2003 WILSON 42. 2009 / 059859A2 May 14, 2009 DB ALLEN 43. 2020 / 142125A2 July 9, 2020 HE Research publications: MO (HEO with rock salt "sodium chloride" crystal lattice structure) 1. CM Rost, Ph.D thesis, North Carolina State Univ (2016), “Entropically-stabilized oxides: Explorations of a novel class of multicomponent materials”. 2. CM Rost, E. Sachet, T. Borman, A. Moballegh, E. Dickey, D. Hou, J. Jones, S. Curtarolo, JP Maria, Nature Communications: 09-25-2015, “Entropy-stabilized oxides”. 3. Moballegh, C. M. Rost, Jon-Paul Maria, E C. Dickey, Microsc. Microanal., 21 (2015), pp. 1349-1350: “Chemical homogeneity in entropy-stabilized complex metal oxides”. 4. Z. Rak, J-P, Maria, D. W. Brenner, Mater Lett: 217 (2018) pp. 300-303: “Evidence for Jahn-Teller compression in the (Mg,Co,Ni,Cu,Zn)O entropy.” 5. C. M. Rost, Z. Rak, D. W. Brenner J.-P. Maria, J. Am Ceramic Society, 100(2017), pp. 2732-2738, “ Local structure of the Mg x Ni x Co x Cu x Zn x (x=0.2) entropy-stabilized oxide: An EXAFS study”. 6. Z. Rak, C. M. Rost, M. Lim, P. Sarker, C. Toher, S. Curtarolo, J. P. Maria, D. W. Brenner, J. App. I Phys., 120 (2016) pp. 95-105, “Charge compensation and electrostatic transferability in three entropy-stabilized oxides: results from density functional theory calculations” 7. G. Anand, A. P. Wynn, C. M. Handley, C. L. Freeman, Acta Mater., 146(2018) pp. 119- 125, “Phase stability and distortion in high entropy oxides” 8. Sarkar, R. Djenadic, N. J. Usharani, K. P. Sanghvi, J. Euro Ceram Soc, 37(2017) pp. 747- 754, “Nanocrystalline multicomponent entropy stabilized transition metal oxide”. 9. D. Berardan, S. Franger, D. Dragoe, A. K. Meena and N. Dragoe, Phys. Status Solidi RRL 10, 4(2016), pp. 328-333, “Colossal dielectric constant in high entropy oxides” 10. D. Berardan, S. Franger, A. K. Meena and N. Dragoe, J. Mater. Chem. A, 24(2016), pp. 9536-9541, “Room temperature Lithium superionic conductivity in high entropy oxides” 11. D. Berardan, A. K. Meena, S. Franger, C. Herrero and N. Dragoe, J. Alloys and Compounds, 704(2017) pp. 693-700, “Controlled Jahn-Teller distortion in (MgCoNiCuZn)O-based high entropy oxides” Google Scholar Crossref , CAS 12. Sarkar, L. Velasco, D. Wang, Q. Wang, G. Talasila, L. de Biasi, C. Kubel, T. Brezesinski, S. Bhattacharya, H. Hahn, B. Breitung, Nature Communications: 08-24-2018. MO2(Environmentally charged and smooth-walled HEO) https: / / doi.org / 10.1103 / PhysRevLett.91.111010 , Google Scholar Crossref , CAS 13. R. Djenadic, A. Sarkar, O. Clemens, C. Loho, M. Botros, V. Chakravadhanula, C. Kubel, S. Bhattacharya, A. Gandhi, and H. Hahn, Mater. Res. Lett. 5(2017), pp. 101-1 102-109, “Multicomponent equiatomic rare earth oxides” . https: / / doi.org / 10.1103 / PhysRevLett.98.1101 , Google Scholar Crossref , CAS 14. K. Chen, X. Pei, L. Tang, H. Cheng, Z. Li, C. Li, X. Zhang, L. An, J. Euro Ceram Soc, 38(2018) pp. 141-168. 4161-64, “A Five-Component Entropy-Stabilized Fluorite Oxide”. 15. A. Sarkar, C. Loho, L., Velasco, T. Thomas; S. Bhattacharya, H. Hahn, R. Djenadic, Dalton Transactions 36(2017), pp. 107-111. 12167-176, “Multicomponent Equiatomic Rare Earth Oxides” 12167-176. 16. J. Gild, M. Samiee, JL Braun, T. Harrington, H. Vega, PE Hopkins, K. Vecchio, and J. Luo, J Euro Ceram Soc. 3578-3584, “High-entropy fluorite oxides” 3578-3584. ABO3 (Architectural Air Force Base and Air Force HEO) Scripta Mater, 142(2018), pp. 17. S. Jiang, T. Hu, J. Gild, N. Zhou, J. Nie, M. Qin, T. Harrington, K. Vecchio, J. Luo. A new class of high-entropy perovskite oxides , pp. 116-120. 18. A. Sarkar, R. Djenadic, D. Wang, C. Hein, R. Kautenburger, O. Clemens, H. Hahn, J Euro Ceram Soc, 38(2018) pp. 101-116. 2318-2327, “Rare Earth and Transition Metal Based Entropy Stabilized Perovskite Type Oxides”. M3O4 (Optimal Wastewater Ornamentation HEO) https: / / doi.org / 10.1103 / PhysRevLett.101.111011 , Google Scholar Crossref , CAS 19. J. Dabrowa, M. Stygar, A. Mikula, A. Knapik, K. Mroczka, W. Tejchman, M. Danielewski and M. Martin, Mater. Lett , 216 ( 2018 ) pp 32-36, “Synthesis and Microstructure of (Co,Cr,Fe,Mn,Ni)3O4High Entropy Oxide Characterized by Spinel Structure”. 20. A. Navrotsky and OJ Klepp. and, J. Inorg. Nucl. Chem., vol.29, no. 11, pp. 2701-2714, 1967, “The thermodynamics of cation distributions in simple spinels”. A2B2O6 (Hypothelial Oxidation Orbital Resistant HEO) 21. Li, F., L. Zhou, Liu, IX, Liang, Y., & Zhang, G. ,L., Journal of Advanced Ceramics, 4(2019), pp, 576-582. 22. Wright, AI, Wang, Q., Ko, ST, Chung, KM, Chen, R., & Luo, I., Structural Materials, 181(2020), pp. 107-111. 76-81, “Size disorder as a descriptor for predicting reduced thermal conductivity in medium-and high-entropy pyrochlore oxides”. 23. Z. Teng, L. Zhu, Y. Tan, S. Zeng, Y. Xia, Y. Wang, & H. Zhang, J Euro Ceram Soc. 1639-1643, “Synthesis and structures of high-entropy pyrochlore oxides”. 24. Ren, K., Wang, Q., Shao, G., Zhao, X., & Wang, Y, Scripla Materialia, 178(2020) pp. 382-386, “Multicomponent high-entropy zirconates with comprehensive properties for advanced thermal barrier coating”. General references 25. A. Giri, J. Braun, C. M. Rost, P. E Hopkins, Scripta Mater., 138(2017) 134-138, “On the minimum limit to thermal conductivity of multi-atom component crystalline solid solutions based on impurity mass scattering” Wear of ceramics 26. J. Jonca, B. Malard, J. Soulie, T. Sanviemvongsak, S. Selezneff, and A. V. Put, Corros. Sci., 153 (2019) 170-177, “Oxidation behaviour of a CoNiCrAlY / h-BN based abradable coating” 27. Y. D. Liu, J. P. Jhang, Z.L. Pei, J. H. Liu, W. H. Li, J. Gong, and C. Sun, Wear, 456-457 (2020) 203389, “Investigation on high-speed rubbing behavior between abrasive coatings and Al / hBN abradable seal coatings” 28. R, Soltani, M. Heydarzadeh-Sohi, M. Ansari, F. Afsari, and Z. Valefi, Surf. Coat. Technol., 321 (2017) 403-408, “Effect of APS process parameters on high-temperature wear behavior of nickel-graphite abradable seal coatings” 29. Y. Cui, M. Guo, C. Wang, Z. Tang, L. Cheng, Surf. Coat. Technol., 394 (2020) 125915, “Evolution of the residual stress in porous ceramic abradable coatings under thermal exposure” 30. X. M. Sun, L.Z. Du, H. Lan, H. F. Zhang, R. Y. Liu, Z. G. Wang, S. G. Fang, C. B. Huang, Z. A. Liu, and W. G. Zhang, Surf. Coat. Technol., 397 (2020) 126045, “Study on thermal shock behavior of YSZ abradable sealing coating prepared by mixed solution precursor plasma spraying” 31. M. H. Foroushani, M. Shamanian, M. Salehi, and F. Davar, Ceram. Int., 42 (2016) 15868-15875, “Porosity analysis and oxidation behavior of plasma sprayed YSZ and YSZ / LaPO4 abradable thermal barrier coatings”
Claims
1. containing a calcia-magnesia-alumina-silicate (CMAS) resistant oxide, A thermal spray material raw material, wherein when the oxide reacts with CMAS having a low melting temperature of 1110°C to 1125°C at 1250°C for 8 hours, the oxide exhibits a CMAS penetration depth of 100 μm or less.
2. The thermal spray feedstock material of claim 1 , wherein the oxide is a high entropy oxide (HEO).
3. The oxide 5 to 14% by weight of alkaline earth metal oxides; 35 to 70 wt. % of a rare earth metal oxide; 6 to 20% by weight of Y 2 O 3 , and The balance is ZrO 2 The thermal spray material feedstock of claim 1 , comprising:
4. The oxide 5 to 9% by weight of alkaline earth metal oxides; 41 to 63 wt. % of rare earth metal oxides; 15 to 24% by weight of Y 2 O 3 , and The balance is ZrO 2 The thermal spray material feedstock of claim 1 , comprising:
5. 4. The thermal spray material feedstock of claim 3, wherein the alkaline earth metal oxide is at least one of CaCO3, CaO, or MgO.
6. The rare earth metal oxide is Yb 2 O 3 , Gd 2 O, or Sm 2 O 3 The thermal spray material raw material according to claim 3, which is at least one of the following:
7. 5. The thermal spray feedstock material of claim 4, wherein the alkaline earth metal oxide is MgO.
8. The rare earth metal oxide is 1 to 2% by weight of La 2 O 3 and 24-38 wt.% Gd 2 O 3 The thermal spray material raw material according to claim 4, which is at least one of the following:
9. Less than 2% by weight of La 2 O 3 or another source of La.
10. 2. The thermal spray material feedstock of claim 1, comprising a total content of costly oxides including at least one of Hf-oxide, Ta-oxide, Dy-oxide, Nb-oxide, Nd-oxide, Gd-oxide, and Y-oxide of 55 wt.% or less.
11. 55% by weight or less of Y 2 O 3 and Gd 2 O 3 5. The thermal spray feedstock material of claim 4, comprising a total content of costly oxides including at least one of:
12. 1. A method for producing an abradable sealing coating, comprising: The method includes the steps of: plasma spraying the thermal spray material according to claim 1 onto a turbine blade or a part of a jet engine; The method, wherein the thermal spray material feedstock comprises an oxide in contact with the turbine blade or the portion of the jet engine.
13. 3. An abradable sealant coating comprising the HEO of claim 2.
14. 14. The abradable sealant coating of claim 13, wherein the HEO has a high configurational entropy of greater than 1.5R.
15. 14. The abradable sealant coating of claim 13 further comprising a thermal barrier coating basecoat.
16. The HEO is represented by the general formula M x O y 14. The abradable sealant coating of claim 13, wherein M is selected from the group consisting of at least five different oxide-forming metal cations.
17. The HEO is represented by the general formula M x O y 14. The abradable sealant coating of claim 13, wherein M is selected from at least one member of Group II of the periodic table.
18. The HEO is represented by the general formula M x O y and M is selected from at least one lanthanide of the periodic table.
19. The HEO is represented by the general formula M x O y 14. The abradable sealant coating of claim 13, wherein M is selected from at least one transition metal.
20. An abradable sealant coating comprising greater than 5 mol % of five or more different oxide-forming metal cations.
21. 16. The abradable sealant coating of claim 15, wherein all of the oxides form a single phase solid solution.
22. 16. The abradable sealant coating of claim 15, wherein multiple oxide phases are present.
23. 16. The abradable sealant coating of claim 15, which comprises a high level of porosity and can have a porosity of about 30-70% by cross-sectional area.
24. 16. The abradable sealant coating of claim 15, comprising at least one fugitive phase.
25. 16. The abradable sealant coating of claim 15, wherein the at least one fugitive phase comprises polyester, talc, and boron nitride.
26. 5-14% by weight of at least one alkaline earth metal oxide comprising CaCO3, CaO, or MgO; 35 to 70% by weight of Yb 2 O 3 , Gd 2 O, or Sm 2 O 3 At least one rare earth metal oxide comprising 6 to 20% by weight of Y 2 O 3 , and The balance is ZrO 2 A high entropy oxide powder comprising:
27. A turbine blade comprising the abradable sealant coating of claim 13.
28. A portion of a jet engine comprising the abradable sealant coating of claim 13.